Digital Shift in Construction in Australia: Unlocking Potential with AI and Blockchain - Gupta, Mansee; Nofal Arif, Rahmanda (Journal of Resilient Economies (ISSN: 2653-1917), 2024)
For any country, the construction industry forms the backbone of economic growth and development. In recent times, Australian construction sector has been struggling to keep up with the increasing demands of economic growth. Being one of the least digitalised industries, the construction industry is facing myriad of challenges including inaccurate cost efficiencies, labour shortages and poor quality management and limited visibility to all the stakeholders. The advancement of digital technologies such as Artificial Intelligence (AI) and Blockchain has proven to be transformational in other sectors such as finance and banking. This research paper examines the benefits of Artificial Intelligence (AI) and blockchain throughout the different phases of the construction project lifecycle. The adoption of AI is met with resistance from leadership and sceptic approach from users. The role of leadership becomes pivotal in widespread adoption of AI and thus changing the attitude of users from “resistance to change” to “receptiveness to change.” Furthermore, various management strategies and recommendations have been discussed in detail to help the leadership teams to accelerate the digital transformation in the Australian construction industry.